Efektivitas Program Pembinaan Kedisiplinan Dalam Proses Belajar Mengajar Terhadap Etos Kerja Mandiri Guru - Rodince Siahaan (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The purpose of this study was to determine the relationship between teaching discipline in the classroom and improving the quality of self-competence for teachers. The research location is SD Negeri 030435 Pardomuan, Kingdom sub-district, involving six teachers. The results showed that in the first cycle, the observation results were "unsatisfactory". In the second cycle showed that the results of the observations were "satisfactory". After carrying out research activities in the teaching and learning process, information was obtained from observations that the teachers at SDN 030435 Pardomuan, Kingdom sub-district had good self-motivation and discipline competencies during the learning process and this would have a positive impact on students both for improving student achievement and for improving student achievement. student's motivation to study.Keywords: discipline; independent work; work ethic Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kedisiplinan mengajar di kelas dengan  peningkatan mutu kompetensi diri bagi para guru. Lokasi penelitian adalah SD Negeri 030435 Pardomuan kecamatan Kerajaan  dengan melibatkan enam orang guru. Hasil penelitian menunjukkan pada siklus I, bahwa hasil observasi "kurang memuaskan". Pada siklus II menunjukkan bahwa hasil observasi "memuaskan". Setelah terjadi pelaksanaan kegiatan penelitian dalam proses belajar mengajar diperoleh informasi dari hasil pengamatan  bahwa para guru di SDN 030435 Pardomuan kecamatan Kerajaan  telah baik dalam memotivasi diri dan komptensi kedisiplinan selama pembelajaran berlangsung dan ini akan berdampak positif bagi siswa baik untuk peningkatan prestasi belajar siswa maupun untuk meingkatkan motivasi belajar siswa.Kata Kunci: disiplin; etos kerja; kerja mandiri